Characterisation of the small regulatory RNA SabS in Acinetobacter baumannii - O'Sullivan, Ciara (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Microbiology, 2026)
Acinetobacter baumannii is a Gram-negative nosocomial pathogen, known for its persistence in harsh environments and increasing antibiotic resistance profile. This pathogen is known for its genomic flexibility, and ability to acquire antibiotic resistance determinants through horizontal gene transfer, conjugation, and outer membrane vesicle mediated transfer. Emerging evidence points towards small RNAs (sRNAs) as a mechanism by which bacteria regulate gene expression post-transcriptionally to respond to environmental stressors, however sRNA mediated gene regulation in A. baumannii remains poorly understood. The development of pulldown methods coupled with high-throughput sequencing, such as Hi-GRIL-seq has advanced understanding of the sRNA biology of pathogens such as A. baumannii. This study focuses on the characterisation of the sRNA SabS, which was shown to be directly regulated at the promoter level by the SigAB sigma factor during copper stress. Previous Hi-GRIL-seq results have identified four putative mRNA targets of SabS: ABUW_RS18870, ABUW_RS00045, ABUW_RS13040, and ABUW_RS15920. During this study these targets were verified in vivo, using the pAMCK 2-plasmid reporter system in both A. baumannii, and E. coli. In addition, the impact of chromosomal sabS and sigAB deletions on the expression levels of these four mRNAs was tested. The AB5075 sabS mutant strain exhibited growth defects when subject to SDS mediated envelope stress, however this phenotype was not observed in the sigAB mutant strain, suggesting an independent role of SabS in mediating envelope stress. Furthermore, Hi-GRIL-seq analysis carried out at early stationary phase uncovered several putative sRNA-containing chimeras, as well as the previously validated interaction between SabS and ABUW_RS00045.
APPROVED